Development of Interactive Learning Media Articulate Storyline Assisted by Canva in Music Arts Regional Song Material Class IV B SDN Kambangan 01 - Dewi Rahma Aprilia; Deni Setiawan (Publikasi Pendidikan, 2026)
This research is motivated by the low motivation of students in learning music, especially related to the material of regional songs in Indonesia. In addition, there is a problem of minimal use of learning media by teachers during the teaching process, as well as deficiencies in teacher competencies that hinder the ability to utilize technology as an educational instrument. The main objective of this study is to develop interactive learning media based on Articulate Storyline as an aid in teaching music with a focus on regional songs in Indonesia. The method used is research and development (R&D) by applying the ADDIE model, which involves five development phases, namely analysis, design, development, implementation, and evaluation. The research subjects included 30 students from grade IV at SDN Kambangan 01. Data collection techniques applied included interviews, observations, questionnaires, and documentation. The data obtained were then analyzed through a descriptive approach that integrates qualitative and quantitative aspects. The results of the study revealed that validation from material experts reached a score of 97.7% with a category of "Very Feasible", while validation from media experts reached 95% with a similar category. The effectiveness measurement showed an average N-Gain score of 0.7544, which is classified as High. Based on these findings, it can be concluded that the Articulate Storyline Interactive Learning Media for learning music arts with regional song material in Indonesia in class IV B SDN Kambangan 01 has been proven valid, practical, and effective, so it is very appropriate to be implemented in learning activities.